2009
DOI: 10.1111/j.1600-0587.2008.05735.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between net primary productivity and foliar carbon isotope ratio across a Tibetan ecosystem transect

Abstract: Warming climate could affect leaf-level carbon isotope composition (d 13 C) through variations in photosynthetic gas exchange. However, it is still unclear to what extent variations in foliar d 13 C can be used to detect changes in net primary productivity (NPP) because leaf physiology is only one of many determinants of stand productivity. We aim to examine how well site-mean foliar d 13 C and stand NPP co-vary across large resource gradients using data obtained from the Tibetan Alpine Vegetation Transects (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 53 publications
8
69
0
Order By: Relevance
“…(1) and (2) indicated that when the E/E m ratio was more than 0.85, NPP varied little with water availability but linearly increased with increasing N mass . The threshold of water limitation of E/E m < 0.85 has been confirmed by the Tibetan transect data (Luo et al 2009). Globally, forest NPP increases with increasing precipitation when annual precipitation is lower than the threshold level of 150 cm (Luyssaert et al 2007) consistent with the Tibetan transect data (Luo et al 2004).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…(1) and (2) indicated that when the E/E m ratio was more than 0.85, NPP varied little with water availability but linearly increased with increasing N mass . The threshold of water limitation of E/E m < 0.85 has been confirmed by the Tibetan transect data (Luo et al 2009). Globally, forest NPP increases with increasing precipitation when annual precipitation is lower than the threshold level of 150 cm (Luyssaert et al 2007) consistent with the Tibetan transect data (Luo et al 2004).…”
Section: Discussionmentioning
confidence: 75%
“…(1). The TAVT data are found in Luo et al (2009) For 1-4(5)-year-old needles, the d 13 C showed significantly positive correlations with air temperature, soil temperature, pan evaporation, and photosynthetically active radiation (p < 0.01) ( Table 2). In contrast, the d 13 C in new and 6-7-year-old needles showed no significant relationships with climatic variables of current year (1999, Table 2) and previous years (1998 and before, data not shown).…”
Section: (A)mentioning
confidence: 91%
“…The sole source of carbon for green plants is air carbon dioxide, and the C 3 photosynthetic pathway is adopted by all study species-aspects that simplify fractionation pathways and determine species' convergent responses. Mixed C 3 -C 4 plant assemblages typical of low latitudes in fact display abrupt divergence in this aspect (Körner et al 1988;Luo et al 2009). Conversely, strong phylogenetic dependence has been found for plant d 15 N and %N, and indeed a greater diversity of functional and physiological mechanisms govern the nitrogen compared with the carbon cycle.…”
Section: Evolutionary Controlmentioning
confidence: 99%
“…; Vitousek et al 1990). These long-and short-term strategies indirectly determine d 13 C variation along elevation (Luo et al 2009) and also explain its responsiveness to changes in growing season precipitation (table 3). The value of d 13 C was also influenced by plant nitrogen content, possibly because of the photosynthetic requirement for this element.…”
Section: Abiotic and Biotic Controlmentioning
confidence: 99%
See 1 more Smart Citation